Growing Cherry and Plum Grafts from Green Cuttings on an Artificial Substrate - Azamovna , Kimsanova Kholida; Nodirbek’s , Rahmatov Mirjalal (Miasto Przyszłości, 2024)
The seedling production process will be effective only if the optimal cultivation technology is used in this, suitable for modern conditions. Therefore, the development and application of promising, innovative and cost-effective technologies that allow the mechanization of working processes related to the cultivation of seedlings in nurseries is an important task.